The New book of popular science. (Dandury, Conn : Groiler, 2002)
1. Astronomy, space science, mathematics.--2. Earth sciences, energy, environmental science--3. Chemistry, physics, biology--4. Plant life, animal life-- 5. Mammals, human sciences-- 6. Technology
Includes bibliographical references and index
Keywords: Science -- Juvenile literature; Technology -- Juvenile literature; Technology -- Popular works; Science; Technology